2019
DOI: 10.2217/cer-2018-0129
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ early engagement in research proposal development (PEER-PD): patients guiding the proposal writing

Abstract: Patient engagement often starts after research funding is secured with little or no involvement of patients in the proposal development phase. This paper compares three levels of patient engagement and describes patients’ early engagement in research proposal development process and its contemporary relevance to clinical and translational research. Authentic patient engagement is illustrated using an example of an ongoing pragmatic clinical trial. The paper also addresses key patient considerations and questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The committee unanimously agreed on the utility and importance of engaging patients in all aspects of research, from planning to disseminating results. Patient advisors, integrated at the clinic and organization level, are increasingly viewed as essential members of the research community ( 17 19 ). Engaging patients early in the research process helps to determine key patient-centered study outcomes, to identify drivers of and barriers to research participation, and to enable patients to take on central roles in overseeing the conduct of PCOR.…”
Section: Considerations and Best Practices For Engaging Patients And Other Key Stakeholders In Pcor In Ildmentioning
confidence: 99%
“…The committee unanimously agreed on the utility and importance of engaging patients in all aspects of research, from planning to disseminating results. Patient advisors, integrated at the clinic and organization level, are increasingly viewed as essential members of the research community ( 17 19 ). Engaging patients early in the research process helps to determine key patient-centered study outcomes, to identify drivers of and barriers to research participation, and to enable patients to take on central roles in overseeing the conduct of PCOR.…”
Section: Considerations and Best Practices For Engaging Patients And Other Key Stakeholders In Pcor In Ildmentioning
confidence: 99%
“…A key finding from our study was that P2P awardees reported that they achieved true patient and stakeholder engagement in their projects -moving beyond 'passive engagement,' where patients are human subjects in clinical research trials and the engagement is researcher-driven and 'tokenistic engagement' where patients and stakeholders provide input but are not true partners in the research [17]. P2P partnerships achieved what Natafgi and colleagues refer to as 'authentic engagement,' characterized by 'long-term partnerships with patients and their communities, including capacity building and enabling and facilitating shared leadership.'…”
Section: Discussionmentioning
confidence: 85%
“…Approaching community members for help late in the process engenders an understandable backlash [21]. Many community members express frustration about being asked to rescue studies in midstream instead of being invited early on to collaborate in designing the project and have ongoing involvement as respected partners.…”
Section: Too Little Too Late?mentioning
confidence: 99%
“…Moreover, PCORI merit review committees include patients and stakeholders in addition to scientists. Evaluations have demonstrated the feasibility and benefits of PCORI's approach, with stakeholder participation in the review process complementing rather than detracting from consideration of a proposal's scientific merit [21,29,30]. The NIH, CDC, AHRQ, SAMSA, and other federal agencies funding research should follow PCORI's precedent.…”
Section: Mid-course Corrections and Best Practicesmentioning
confidence: 99%